Social determinants of an occupational lung disease: Workers' narratives on silicosis - Yanni Liang; Katherine E. McCoy; Carrie D. Tomasallo; Jonathan G. Meiman (Elsevier, 2023)
Silicosis is a preventable occupational lung disease caused by inhaled silica dust. Solutions to prevent silicosis ranging from engineering controls to respirator use have been validated for nearly a century, but many workers are still at-risk of this preventable disease. We characterized how the physical, social, and institutional environments contribute to silicosis and health disparities. Using semi-structured interview responses from people living with silicosis in Wisconsin, U.S., we inductively coded participants' experiences from occupational exposure to navigating healthcare and assistance. Codes explaining the data patterns and research questions were constructed into three themes: 1) "Education and Labor Market Relationships Converge to Increase Silicosis Risk" describes how educational attainment and employment arrangements contribute to silicosis risk, 2) "On the Job" describes work-relatedness of silicosis and how organizational cultures and socialized masculine norms influence prevention, and 3) "Off the Job" illustrates how structural barriers obstruct workers' access to care and assistance when they have silicosis. Findings illustrated that institutions and sociocultural values can lead to inequitable distribution of occupational risks and mitigation resources relating to silicosis, including access to healthcare and worker's compensation, and they compound to worsen health inequity. In demonstrating how multiple socioeconomic forces perpetuate and minimize silicosis risk, we show that work is a social determinant of health. We further highlight that qualitative data can enhance public health surveillance by contextualizing people's experiences of disease.